MODEL PEMBELAJARAN DISPERSI IMAJINASI: UPAYA MENGEMBANGKAN KETERAMPILAN MENULIS CERPEN PADA ERA INDUSTRI KREATIF - Ruli Andayani (Universitas Muhammadiyah Ponorogo, 2016)
Indonesia follows the global trend entering the creative industries, including the publication of literary works. It is a challenge for educationists to inculcate creativity among students literary writing. Students are expected to be a productive man in composing short story as stated in the 2013 curriculum. Considering this, the dispersion learning model is designed for students to learn writing a short story, achieving learning goal planned, and realize the goals of national education. The learning model is not only allows student to be creative and productive in writing short story, but also emphasize discussion in group with mutual support. Since the eginning of learning, students were involved in group, while the teacher acts as a facilitator, motivator, and inspirator. The learning procedure includes six activities: watch, share, give character figure, thugh, exercise, and publish.